Experience, Training, and Tools: A Mixed-Methods Study of Decision-Making for Obstetric Transport in a Rural State [A279]. (May 2022) - Yi, Avalon; Miller, Bailey; Sandoval-Belt, Payton; Patel, Juhee; Quiner, Trevor
Abstract : INTRODUCTION: New Mexico relies heavily on emergency obstetric transport due to the widely separated rural communities and limited centers for providing advanced maternal, fetal, and neonatal care. Emergency transport requires careful decision making and efficient use of resources. This study aims to evaluate perceived adequacy with respect to training, experience, and resources for obstetricians who make transport decisions. METHODS: An interview guide and survey questions were developed to evaluate the perception of different aspects of emergency obstetric transport in New Mexico. Interviews were performed with obstetrics and gynecology providers who participate in emergency obstetric transport, both sending and receiving, throughout the state of New Mexico in both rural and urban communities. Interviews were recorded, transcribed, and coded for qualitative analysis. RESULTS: The majority (75%) of participating providers had no formal training in emergency transport during their medical education, and there was a common sentiment that targeted training in obstetric transports would be beneficial. However, providers who reported being uncomfortable in making transport decisions at the beginning of their current positions reported quickly gaining the experience needed to feel comfortable. Although tools to assess preterm labor are extremely limited in some settings (transvaginal cervical length available to only 40% of interviewees), all providers felt that they had the necessary tools to make transport decisions. CONCLUSION: Obstetric transport is essential in rural obstetric care. Although experience is an excellent teacher, obstetric training is generally lacking in transport-focused education. Development of obstetric transport-centered training may improve the comfort level of providers in new settings.